Graph-based map representations for efficient path planning in virtual environments - Wardhana, Nicholas Mario (2016)
Path planning is fundamental in various Computer Graphics (CG) applications to determine a character's path so that it can move from one location to a new location in a virtual environment. Path planning requires a map of the environment to work, as it acts as a spatial knowledge for the characters. Some examples of existing map representations are waypoint graph, roadmap, and navigation mesh.